DIFFERENT POTTING MIX ON FORMATION OF WITHIN-PACKAGE SEEDLINGS OF PEACH - PICOLOTTO, Luciano; BIANCHI, Valmor João; GAZOLLA NETO, Alexandre; FACHINELLO, José Carlos (Scientia Agraria, 2007)
In Brazil, most of the nursery peach trees marketed sold to the fruit growers has been as bare-root plants during their dormancy during the winter. However, potted nursery trees may be a high potential choice for different planting time during the year. This research aimed to assess the influence of different substrates on development of peach rootstocks and cultivar ‘Maciel’ raised in package. The tested substrates were equal volume combinations: Plantmax®HT + húmus + sand; Plantmax® HT + húmus; Plantmax® HT + húmus + calcined rice hulls. The rootstock seeds were treated with Pro-Gibb® at 200mg.L-1 concentration during 16 hours, previously to their planting in the pots with the referred substrates. After 180 days the seedlings were evaluated about the following variables: trunk diameter; tallness; canopy volume and dry mass per plant. At the budding time (180 days after the beginning of seed germination), the larger trunk diameter averages were observed on Okinawa, reaching 5,9 mm in pots with Plantmax®HT + húmus+calcined rice hulls and 5,8 mm in pots with Plantmax®HT + húmus + sand substrates, whereas in “Aldrighi” seedlings were 5,5 mm with Plantmax®HT + húmus + sand and 5,4 mm with Plantmax®HT + húmus substrates. Regarding to plant height, the tallest plant was those of cv. Capdeboscq in Plantmax®HT + húmus substrate which averaged 46,6 cm, whereas the higher dry mass average of the seedlings were observed in the plants grown in the Plantmax®HT + húmus substrate. At the end of the growth season the larger rootstock trunk diameter average was observed in the plants grown in Plantmax®HT + húmus substrate (7,6 mm). Regarding to canopy volume and plant height at the end of the growth season, there was no influence of the substrates.